Mengoptimalkan Manajemen Persediaan: Pelatihan Aplikasi Stok untuk Daya Saing UMKM Bucin Latte & Telogut - Annisa, Adela Putri; Ariadi, Adella Putri; Purnomo, Adella Wahyu; Mawarni, Adila Widya Nisa; Handayani, Adinda Putri; Putri, Oktaria Ardika (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This service aims to increase the efficiency of inventory management at Bucin Latte and Telogut MSMEs through the implementation of the "Warehouse Inventory Stock" application. Through an implementation method that involves direct training for owners and employees, manual use of stock recording is replaced with digital applications. As a result, we can see increased efficiency, reduced risk, and more accurate, effective, and optimal stock recording. The implementation of this application not only increases the productivity and operational efficiency of Bucin Latte and Telogut but also provides great potential to compete in the market and achieve sustainable growth. Thus, this service makes a positive contribution to optimizing inventory management for MSME sales products and minimizing losses in their business.